Media literacies : a critical introduction - Hoechsmann, Michael; Poyntz, Stuart R. (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
"Whether we like it or not, communication technologies -- ever smaller, more convergent, and comprehensive -- are tightly woven into the cultural fabric of our everyday lives. How did we get here? And what exactly does it mean to be 'literate' in this new media era? Media Literacies: A Critical Introduction traces the history of media literacy and grapples with the fresh challenges posed by the convergent media of the 21st century. The book explores the history and emergence of media education, contemporary youth and its digitally mediated lives, digital literacy, and critical citizenship. Sidebar commentary written by leading media researchers and educators spotlights specific issues and media phenomena. Media Literacies provides students and educators alike with an invaluable theoretical and practical approach to understanding media literacy in the remarkable digital age we find ourselves in"--
"Media Literacies: A Critical Introduction traces the history of media literacy and grapples with the fresh challenges posed by the convergent media of the 21st century. The book provides a much-needed guide to what it means to be literate in today's media-saturated environment. Updates traditional models of media literacy by examining how digital media is utilized in today's convergent culture Explores the history and emergence of media education, the digitally mediated lives of today's youth, digital literacy, and critical citizenship Complete with sidebar commentary written by leading media researchers and educators spotlighting new research in the field and an annotated bibliography of key texts and resources "--
Includes bibliographical references and index.
Print version record.
Keywords: Media literacy; Digital media; SOCIAL SCIENCE -- Media Studies; Digital media; Media literacy; Massamedia; Jeugd; Vaardigheden; Electronic books